THE DIAGNOSIS OF INTRA-ABDOMINOPELVIC LESIONS USING IMAGE-GUIDED FINE NEEDLE APRYLATION CYTOLOGY - PAHADIYA, POOJA; CHOUDHARY, SUNIL; MADHUR, ALANKRITA (International Journal of Current Pharmaceutical Research, 2024)
Objective: This study aims to evaluate the efficacy of image-guided fine needle aspiration cytology (FNA) in diagnosing intra-abdominopelvic lesions, emphasizing the synergy between minimal invasiveness and high diagnostic accuracy. Methods: A retrospective analysis of 200 cases where image-guided FNA was employed for intra-abdominopelvic lesions was conducted. The procedures were performed under USG or CT guidance, with needle placement and specimen adequacy closely monitored. Cytological findings were processed and classified according to the latest WHO guidelines, with diagnostic accuracy assessed through comparison with subsequent histopathological findings where available. Results: The study found that liver, ovaries, and pancreas were the most common sites of lesion, comprising 25%, 20%, and 15% of cases, respectively. Cytological analysis revealed that 60% of lesions were benign, 20% malignant, with the remaining 20% classified as non-diagnostic or suspicious. Radiological findings were crucial in guiding FNA, with solid masses accounting for 50% of cases. An impressive concordance rate of 87.85% between cytological and histopathological diagnoses highlighted FNA's reliability. Conclusion: Image-guided FNA proves to be a minimally invasive, accurate, and cost-effective diagnostic tool for intra-abdominopelvic lesions, with significant implications for patient management and care. The high concordance rate with histopathological findings underscores its diagnostic reliability, advocating for its continued development and integration into clinical practice.